Responding to N.T. Wright's Rejection of the Soul - Rickabaugh, Brandon L. (2018)
At a 2011 meeting of the Society of Christian Philosophers, N. T. Wright offered four reasons for rejecting the existence of soul. This was surprising, as many Christian philosophers had previously taken Wright's defense of a disembodied intermediate state as a defense of a substance dualist view of the soul. In this paper, I offer responses to each of Wright's objections, demonstrating that Wright's arguments fail to undermine substance dualism. In so doing, I expose how popular arguments against dualism fail, such as (1) dualism is merely an unwarranted influence of Greek culture on Christianity, and (2) substance dualism is merely a soul-of-the-gaps hypothesis. Moreover, I demonstrate that Wright himself has offered a powerful reason for adopting substance dualism in his previous works. In conclusion I offer a view that explains why the human soul needs a resurrected body.